Examining the Mediating Role of Test Anxiety in the Relationship between Procrastination and Self-Handicapping of Students - Ali Asghar Hayat; Hajar Kiani; Ghobad Ramezani; Mohammad Hassan Keshavarzi (Strides in Development of Medical Education)
Background: Procrastination is a common phenomenon affecting many aspects of personal and academic life, especially among students.Objectives: This research aims to examine the mediating role of test anxiety in the relationship between procrastination and self-handicapping of students in a structural equation modeling approach.Methods: The present research was a cross-sectional study of descriptive-correlational type, performed in 2022 on 200 students. The census method was used for sample selection because of the limited sample size. Three standard questionnaires were used: Solomon and Rothblum Academic Procrastination, Sarason Anxiety Scale, and Johns and Rodwelt Self-Handicapping Scale. Structural equation modeling was used through AMOS 22 with a significance level of 0.05 for data analysis.Results: The findings indicated that procrastination had a positive and significant effect on test anxiety (β = 0.46, p < 0.001) and self-handicapping (β = 0.32, p < 0.001). Also, the impact of text anxiety on self-handicapping (β = 0.49, p < 0.001) was positive and significant. There was also an indirect effect of procrastination on the self-handicapping of students through text anxiety (0.22), which was obtained as positive and significant at 0.01 levels via the Bootstrap method.Conclusion: Procrastination causes increased self-handicapping of students and test anxiety, which promotes further self-handicapping.